Labor Exploitation in The Menu (2022) - Rahmania, Ellen (LITERA KULTURA : Journal of Literary and Cultural Studies, 2025)
This study examines the depiction of labor exploitation in The Menu (2022) using Marxist theories. By focusing on the relationship between Chef Slowik and his kitchen staff, this study analyzes how exploitative labor conditions can lead to alienation and suicide. Using a qualitative method, the film is thematically analyzed through dialogue, visuals, and character interactions. The study draws on the theories of Karl Marx to explore the themes of surplus value, false consciousness, and different forms of suicide. The menu shows that in extreme capitalism, death is not simply the end of life, but can also be a symbol of critique, rejection, and liberation. using the concept of alienation. These three deaths, although different in form and context, share the understanding that when work, identity, and the value of life are completely taken over by the capitalist system, alienation can push individuals and collectives towards inevitable destruction.The findings reveal how capitalist pressures in a stressful environment can lead to psychological disorders and fatal consequences.